Group 12 and 13 metal-alkenyl promoted generation of long-chain branching in metallocene-based polyethylene. (15th June 2022) - Santoro, Orlando; Piola, Lorenzo; Mc Cabe, Karl; Lhost, Olivier; Den Dauw, Katty; Fernandez, Alvaro; Welle, Alexandre; Maron, Laurent; Carpentier, Jean-François; Kirillov, Evgueni
Graphical abstract: Highlights: Discrete B-, Al-, Mg- and Zn-alkenyl species, namely B(pent-4-enyl)3 (B-2 ), Al(pent-4-enyl)3 (Al-2 ), Mg(pent-4-enyl)2 (Mg-2 ) and Zn(oct-7-enyl)2 (Zn-1 ), were used as long-chain branching promoters. Ethylene polymerization with rac -EBTHIZrCl2 (Zr-1 ) and ( n BuCp)2 ZrCl2 (Zr-2 )/MAO systems in the presence of the M−alkenyl co-reactants was studied. The use of B-2 and Al-2 induced a change of the rheological behavior of the PEs compatible with the formation of LCB. PEs obtained with B-2 were characterized as cross-linked structures incorporating hydrolytically stable B-centered branches. DFT calculations were in agreement with the experimental data. Abstract: In situ synthesis of topologically modified linear polyethylenes (PEs) using single-site polymerization catalysis is a challenging task that enables the production of advanced materials with tailored properties. We describe here our investigations aimed at an efficient generation of long-chain branches (LCB) in linear PEs using discrete B-, Al- and Zn-alkenyl co-reagents in combination with homogeneous rac -EBTHIZrCl2 (1 )/ or ( n BuCp)ZrCl2 (2 )/MAO catalytic systems. As corroborated by extensive rheological studies and 13 C NMR spectroscopy, Al-and Zn-based reagents promote LCB formation via a two-step mechanism involving both vinylic group insertion and M → Zr transmetallation steps. In striking contrast, the B-alkenyl species was found to form hydrolytically stable B-centred cross-linked PE structures. The Mg-based reagent appeared to be reluctant towards Mg → Zr transmetallation reaction, providing only the products of vinylic group insertion, which after hydrolysis afforded short-chain branched (SCB) PEs. The experimental observations were rationalized by DFT computations.